(untitled) (Revista de Ciências Agroveterinárias, 2015)
Cape gooseberry (Physalis peruviana) is an exotic plant that belongs to the Solanaceae family. Its cultivation is still little explored in Brazil, but it is a new option for diversification for small farmers. The plant can reach two meters tall using a training system and pruning practices. The objective was to evaluate the behavior of cape gooseberry plant on the Southern Plateau of Santa Catarina, Brazil, in different training systems and spacing. We tested four training systems (free system, vertical trellis system, system in “X” and system in “V”), two spacing (3.00 x 0.50 m and 3.00 x 1.00 m), and 11 evaluation periods during the growing seasons 2008-2009 and 2009-2010. Cape gooseberry plants showed average length of the main branches of 2.48 meters and 15.25 millimeters in diameter. Cape gooseberry plants grown using the system ”V”, under the spacing 3.00 x 1.00 meters, showed the highest diameter of the branches. Plants grown in free systems, vertical trellis system, and system in “X”, with spacing 3.00 x 0.50 meters, provided higher productivity of the cape gooseberry in conditions of Southern Santa Catarina Plateau, Brazil.